Improving the timing accuracy of SiPMs by time‐walk compensation. Issue 3 (1st February 2017) - Acconcia, Giulia; Cariaggi, Davide; Labanca, Ivan; Rech, Ivan; Ghioni, Massimo
Abstract : Timing measurements with silicon photomultipliers (SiPMs) are affected by the major issue of the so‐called time‐walk effect; this is due to the intrinsic architecture of SiPM devices. A new technique for time‐walk compensation in timing measurements with SiPMs is presented and discussed, feasible with a low‐complexity and low‐cost circuitry and able to improve the timing accuracy. The validity of the presented technique has been experimentally proven with a 3 × 3 mm 2 Hamamatsu MPPC, achieving a jitter reduction of a factor 2.85 compared with the case without time‐walk compensation. To perform the experimental validation, a discrete‐components transimpedance amplifier is developed with large bandwidth and low jitter, specifically designed to read‐out and amplify the SiPM signal.